ADHD in Adults: A Systematic Review and Meta-Analysis of Prevalence Studies in Outpatient Psychiatric Clinics. Issue 12 (October 2022) - Adamis, Dimitrios; Flynn, Caroline; Wrigley, Margo; Gavin, Blánaid; McNicholas, Fiona
Objective: Systematic review and meta-analysis to estimate the pooled prevalence of ADHD in adult attendees of outpatient mental health clinics and to investigate factors influencing prevalence rates. Methods: The following were extracted: demographics, design of the study (screening only or two-phase), scales/criteria for diagnosis of ADHD, number of ADHD, and non-ADHD participants. Results: The pooled prevalence of ADHD from screening studies ( n = 9) was 26.7%, (95% CI [17.2–37.4]), ADHD = 1727, No ADHD = 3, 578. From studies employing a two-stage design ( n = 5), prevalence was 14.61%, CI [10.39–19.41], ADHD = 561, No ADHD = 3, 578. Age and gender did not have any significant effect on the estimated prevalence. By contrast exclusion of psychotic disorders lowers prevalence. The screening scale used also influence prevalence rates. Conclusion: Meta-analysis shows high rates of adult ADHD among psychiatric outpatient clinics. Applying DSM-5 criteria increased prevalence rates. More methodologically robust studies, using two-stage design, need to be conducted to help assist in service planning.